Influence of thermal degradation on the crystallization of poly(butylene terephthalate) - Ahmed Nasr; Petr Svoboda (eXPRESS Polymer Letters)
Our work reveals a notable shift in the crystallization temperature (Tc) of poly(butylene terephthalate) (PBT) at which crystallization occurs due to exposure to prolonged thermal degradation at 270°C in an environment of nitrogen gas. The initial Tc of 193°C undergoes a marked decrease, settling at 133°C, which signifies a considerable 60°C shift towards lower temperature ranges. This transition is discernible across three distinct degradation stages: an initial phase of increase, an intermediate phase characterized by a sharp decline, and a subsequent late stage of the degradation phase characterized by a more moderate decrease in Tc. Both crystallinity and crystallization kinetics consistently mirror this pattern, demonstrating an initial rise, a rapid subsequent drop, and a gradual decline in the late-stage period. Evident from the presence of two melting peaks, the research implies differing lamellar thicknesses. As the degradation progresses, the melting points of these peaks, denoted as Tm1 and Tm2, decline at 38 and 41°C, respectively. Validation of the degradation-induced changes is provided by a small angle X-ray scattering (SAXS), which corroborates the observed decrease in the long period (L). A contextualization of the results against prior studies underscores analogous trends in the alteration of crystallization behaviour consequent to degradation.